2006
DOI: 10.4049/jimmunol.177.8.5659
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of CD11c by Peripheral Blood NK Cells Reflects Temporal Activity of Multiple Sclerosis

Abstract: Multiple sclerosis (MS) is an autoimmune disease, showing a great degree of variance in temporal disease activity. We have recently demonstrated that peripheral blood NK cells biased for secreting IL-5 (NK2 bias) are associated with the remission state of MS. In this study, we report that MS patients in remission differentially express CD11c on NK cell surface (operationally defined as CD11chigh or CD11clow). When we compared CD11chigh or CD11clow patients, the expression of IL-5 and GATA-3 in NK cells suppose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 33 publications
1
53
0
Order By: Relevance
“…Although both CD56 br ight and CD11c dim human NK cells have been correlated with multiple sclerosis activity [17], [18], [35], differences in the CD11c expression have not been reported for human NK cell subsets. Analyzing PBMCs from normal donors we observed that CD3 − /CD56 dim NK cells contained a sub-population that expressed high amounts of CD11c (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Although both CD56 br ight and CD11c dim human NK cells have been correlated with multiple sclerosis activity [17], [18], [35], differences in the CD11c expression have not been reported for human NK cell subsets. Analyzing PBMCs from normal donors we observed that CD3 − /CD56 dim NK cells contained a sub-population that expressed high amounts of CD11c (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Among these patients, a further division of NK2 cells as CD11c-high (not producing IL-5) and CD11c-low (producing IL-5) subsets identified CD11c-high patients at risk of relapse (49), suggesting that CD11c + NK cells are pro-inflammatory. In another study, a subpopulation of NK cells characterized by low expression of CD8, a phenotype associated with CD56 bright NK cells, was observed to be reduced in untreated patients with relapsing-remitting MS (50).…”
Section: Possible Role Of Nk Cells In Ms and Its Animal Modelmentioning
confidence: 99%
“…[18][19][20][21] HLA-DR is suitable for this purpose as it is expressed stably for a long duration on activated lymphocytes. 18,21 We found that NKG2A À CD56 dim conjunctiva NK cells were the only activated NK subset, and HLA-DR was not upregulated in the CD56 bright NK cells and NKG2A þ CD56 dim NK cells (Figure 3f,g). CD38 expression was similar to that of HLA-DR where higher expression levels were observed on CD56 dim NK cells and CD56 dim NKG2A À NK cells as compared with CD56 bright and CD56 dim NKG2A þ NK cells respectively (Figure 3h, top panel).…”
Section: Resultsmentioning
confidence: 99%